Risk management techniques in portfolio optimization : weighted conditional value at risk. - Fu, Jingyu. (2008)
LP computable risk measures can be solved using LP solver and become more popular recently. CVaR is a LP computable risk measure, it is the tightest convex approximation of VaR. In this report, we also focus on WCVaR model, which is the weighted sum of CVaR measures at difference confidence levels. We study the theoretical properties of CVaR and WCVaR, develop the algorithm WCVaRMin to solve WCVaR problem, and test the performance of risk models and algorithm using real life data.